Judicial Precedents on Privacy Rights: Court Rulings in the Digital Era (Indonesian Court and Justice Review, 2024)
As digital technologies become increasingly embedded in everyday life, courts in Indonesia are increasingly required to define the scope and limits of privacy rights. This study examines judicial precedents that address privacy in the context of surveillance, data protection, and digital expression, particularly in light of the absence of a comprehensive data protection law until recently. Using qualitative content analysis of Constitutional Court and Supreme Court decisions, this research investigates how Indonesian courts have interpreted privacy within constitutional and statutory frameworks. The findings show a growing recognition of privacy as a fundamental right, though judicial reasoning remains inconsistent and often lacks a clear doctrinal foundation. In several landmark cases, courts have acknowledged the importance of protecting personal data and private communications, but have struggled to balance privacy with competing state interests such as national security or public morality. This study highlights the urgent need for a coherent judicial approach to privacy, especially as digital surveillance and data misuse become more prevalent. The novelty of this research lies in mapping the evolving jurisprudence on privacy and proposing a normative framework for more consistent judicial protection. By critically analyzing court practices, the study contributes to ongoing discussions about constitutional rights in the digital age and the role of judicial precedents in shaping data governance.